Pengembangan Model Fungsi Sosial Bisnis Islam Berdasarkan Maqashid Syariah Pada Bank Syariah X - Muhammad Nafik; R. Moh Qudsi Fauzy (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
Abstract The purpose of this study was to determine the concept of the social function of business model development Islam, especially Islamic Bank X based maqashid sharia, practice development of the social functions of Islamic business models based on the sharia maqashid Islamic Bank X, and the impact of the development of the social functions of Islamic business models based on the quality of sharia maqashid life of the community. This study uses descriptive qualitative research methodology case study method (case study). Criteria informant was branch manager, supervisor, and citizens who have been the target/target activities of social function. The sampling technique is done with purposive sampling and snowball sampling. These results indicate that the concept of the social function of business model development Islam, especially Islamic Bank X based maqashid sharia has had an important role in creating justice and prosperity based on the principles of Shari’ah maqashid especially the external community. Practice development of the social function of the business model of Islam based on sharia maqashid has had a big role in terms of fighting and reduce disorientation in religion (hifdhud-din), the maintenance of stupidity (hifdhul-’aqal), terjauhkannya of poverty (hifdhul maal), has a good offspring (hifdhun-nasl), and maintaining a healthy soul (hifhdun-nafs), and the impact of the development of the social function of the business model of Islamic sharia maqashid based not only on improving the quality of life of citizens around the location of Bank Syariah X which has a weak economy, but also an impact positively to the image of the Islamic Bank X in the minds of customers and other parts of society.